2020
DOI: 10.18280/ijht.380109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Flow Around Two Side-by-Side Circular Cylinders at High Reynolds Number

Abstract: The fluid flow around a cylinder is one of the classic issues in fluid mechanics because of its various applications. Cylindrical structures, both single and in the group patterns, are present in the design of cooling systems of nuclear power plants, hydro-structures, heat exchangers, chimneys, high buildings, power lines, cables and networks in air and water. In many engineering applications, Karman's vortex shedding produces flow-induced vibrations. To comprehend the fluid structures surrounding the cylinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…The study reveals that some specific aspect ratios may lead to vortex shedding, while others exhibit more stable flow patterns. Rahimi, H., et al (Rahimi et al, 2020) numerically presented a comprehensive study of flow behavior between two side-by-side (SBS) circular cylinders at large Reynolds number 1× 10 6 with eleven different gaps spacing to cover both laminar and turbulent flow regimes. They observed that for different gap spacing of cylinders led to variations in the vortex shedding frequency and intensity, impacting the aerodynamic forces experienced by the cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The study reveals that some specific aspect ratios may lead to vortex shedding, while others exhibit more stable flow patterns. Rahimi, H., et al (Rahimi et al, 2020) numerically presented a comprehensive study of flow behavior between two side-by-side (SBS) circular cylinders at large Reynolds number 1× 10 6 with eleven different gaps spacing to cover both laminar and turbulent flow regimes. They observed that for different gap spacing of cylinders led to variations in the vortex shedding frequency and intensity, impacting the aerodynamic forces experienced by the cylinders.…”
Section: Introductionmentioning
confidence: 99%
“…The geometric shape of the cylinder strongly influences the wake behind a cylinder on the hydrodynamic forces. Several articles and scientific research papers based on the study of this physical phenomenon and the importance of the problem have been found [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the vertical arrangement of two cylinders on the flow with a high Reynolds number was studied via numerical modeling by Rahimi et al [2] The results indicated that the flow pattern is irregular and unstable for denser arrangements, while the propagation of the vortices has no tendency in different spacings. The numerical results by Sohankar et al [6] at Reynolds Re = 70-150 and a Prandtl number Pr = 0.71, with the shear rate K = 0-0.2 for flow around two square cylinders in tandem, found that the amplitude of lift increases linearly with K. For Re = 150 to 500, Roshko [9,10] observed an irregular regime with turbulent velocity fluctuations accompanying the periodic formation of vortices.…”
Section: Introductionmentioning
confidence: 99%
“…An Analytic solution of the problem of flow of a micropolar fluid over moving cylinder taking into consideration axisymmetric stagnation flow has been introduced by Rehman et al [7] and Rasheed et al [8] have presented a study that gives a good view of the electrically conducting boundary layer flow of viscoelastic incompressible nanofluid which flows due to a moving linearly stretching surface. More recent papers of the subject of boundary layer flow over a cylinder can be found in the references [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%